Examining countermovement jump strategies between women's NCAA Division I sports - Donahue, P. T.; Peel, S. A.; Rush, M.; McInnis, A. K.; Littlefield, T.; Calci, C.; Brutofsky, T. (The Journal of Strength and Conditioning Research, 2023)
The purpose of this study was to examine countermovement vertical jump performance among female athletes who rely heavily on vertical jump performance within their given sport. Forty-five female athletes representing 3 teams (basketball, volleyball, and beach volleyball) competing at the NCAA Division I level completed 2 maximal effort countermovement jumps (CMJ) using a portable force platform. A 1-way analysis of variance was used to compare groups across each variable. Statistically significant differences were found between the groups regarding propulsive duration and time to takeoff with basketball showing the shortest time and beach volleyball having the longest times (p < 0.05). In addition, differences were seen in countermovement depth and mean propulsive force between the groups with basketball displaying the smallest countermovement and highest force (p < 0.05). No differences were seen in jump height and reactive strength index modified. Greater force and shorter durations in basketball athletes versus the low force and long durations in the beach volleyball athletes suggest that sporting backgrounds play a large role in how the CMJ is performed. This information can aid strength and conditioning practitioners in the design of training programs that are sport specific to the strategies used by the athlete.